The development of a scale to measure young millennials' motivations to get entertainment and information - Konstantyner, Isabela da Cruz Barreto (2020)
According to an informal interview with the marketing manager of Nestlé in Europe, Fast Moving Consumer Goods companies are still struggling and spending a lot of time and money on researches to understand which are the real sources that millennials get entertainment and information from, in order to understand their habits and hence, place their managing decisions accordantly. The millennial generation is expected to become demographically and economically important to companies but at the same time, there is a lack of tools to help managers understand their motivations – such as a motivational scale. Because of that, and due to the lack of academic literature regarding the younger part of this generation (people born between 1990 and 1996), this research aims to explore the different motivational aspects that make young millennials search for entertainment and information in different sources. In order to achieve that goal, the author will go through the current academic literature regarding the topic and develop a motivational scale that, together with quantitative and qualitative analyzes, will bring a tool to help managers understand young millennials’ motivations to achieve a desired goal. By understanding the expected rewards of this group of people, the managing decisions become more assertive and consequently more reliable to be made in a managerial level.